State of play : the role of music therapy in Northern Ireland - Scullion, Conor (2019)
In a population that experiences traumatic events, there will inevitably be resultant mental and physical health problems. This research paper investigates the current role of music therapy in addressing some of these types of health problems in Northern Ireland, a place where civil conflict officially ended in 1998. This research is based on a review of existing literature and research around trauma in Northern Ireland, supplemented by interviews with two music therapists currently practising in Northern Ireland. The purpose of these interviews is to highlight the therapists' own experiences of working in a post conflict society and to discover if music therapy plays a role in their treatment of conflict related health issues. Potential outcomes from this investigation include; getting a better understanding of individual music therapists' own awareness of conflict related problems in their client groups, and understanding how therapists operate in a historically divided society. Identifying the main types of client populations music therapists in Northern Ireland work with is also of value. The larger implications of this study are that it can identify potentially successful strategies for dealing with conflict related illness that could be adapted and employed by other voluntary sector healthcare services. It might also be use ful for music therapists in other conflict areas around the world to gain insight into how therapists in Northern Ireland deal with trauma related illnesses.